Manifestations of functional dyspepsia in case of resentment emotions - Korshevnyuk Дмитро (Psychosomatic Medicine and General Practice, 2018)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" Congress. It is dedicated to the manifestations of functional dyspepsia in case of resentment emotions.